Just Taxation in the Roman Catholic Tradition - Curran, Charles E. (Journal of religious ethics, 1985)
There is general agreement about the very broad outlines of a just tax structure in the Roman Catholic tradition, and these are sketched in part I. There has been, however, no sustained, systematic, in-depth treatment of the question. Part II develops those aspects of the Roman Catholic ethical tradition which ground a just tax structure-the role of the state in working for the common good, distributive justice with its proportional equality, the universal destiny of the goods of creation to serve the needs of all. In addition, some attention is given to the historical practice of tithing, the state's obligation to care for the poor, and the moral obligation to pay just taxes. Part III proposes the goals which should govern a just tax structure in the Roman Catholic perspective and defends these goals against other possible interpretations.